SUMOylation of spastin promotes the internalization of GluA1 and regulates dendritic spine morphology by targeting microtubule dynamics - Zhi-Sheng Ji (Neurobiology of Disease, 2020)
Dendritic spines are specialized structures involved in neuronal processes on which excitatory synaptic contact occurs. The microtubule cytoskeleton is vital for maintaining spine morphology and mature synapses. Spastin is related to microtubule-severing proteases and is involved in synaptic bouton formation. However, it is not yet known if spastin can be modified by Small Ubiquitin-like Modifier (SUMO) or how this modification regulates dendritic spines. Spastin was shown to be SUMOylated at K427, and its deSUMOylation promoted microtubule stability. In addition, SUMOylation of spastin was shown to affect signalling pathways associated with long term synaptic depression. SUMOylated spastin promoted the development of dendrites and dendritic spines. Moreover, SUMOylated spastin regulated endocytosis and affected the transport of the AMPA receptor, GluA1. Our findings suggest that SUMOylation of spastin promotes GluA1 internalization and regulates dendritic spine morphology through targeting of microtubule dynamics.